Spatial Distribution of Traditional Market in Padang City - Chairul Ichsan; ELVI ZURIYANI; Afrital Rezki (USN Kolaka, 2020)
This study aims to spatial distribution of traditional markets in Padang City that which consist of: 1) Distribution spatial of traditional market, 2) Spatial patterns of tradional market, and 3) Range pattern of traditional market. Type of this research is descriptive research with spatial analysis technique. Population in this study are all traditional markets in the Padang City. Sample of this study was that all traditional markets in Padang were taken with a sampling technique. That is total sampling where the number of samples is equal to the population. The data analysis technique uses the analysis of the nearest neighbor index and buffer zone. The results of this study were found that: 1) Spatial Distribution of Traditional Markets in Padang City, there are 21 traditional markets spread across 9 Subdistricts: Koto Tangah District, Padang Utara District, Padang Barat District, Padang Timur District, Padang Selatan District, Lubuk Begalung District, Lubuk Kilangan Subdistrict, Kuranji Subdistrict, and Nanggalo Subdistrict, 2) The distribution pattern of traditional markets in Padang City is included in the pattern of uneven distribution (random), 3) Range pattern of traditional markets in Padang City with a radius of 5Km are more likely to focus in the city center or the western and northwestern parts of Padang City.